Digital hermeneutics as hermeneutics of the self - Romele, Alberto (2022)
In this article, the author deals with the status of the self and personal identity in the digital milieu. In the first section, he presents his general approach to digital media and technologies, which he has called “digital hermeneutics.” He distinguishes between three perspectives in digital hermeneutics, namely the deconstructive, epistemological, and ontological approaches. In the second part, he focuses on digital hermeneutics as hermeneutics of the self. He compares Paul Ricoeur’s narrative identity to Pierre Bourdieu’s habitus. His first thesis is that the habitus can be seen as a concept of subjectivation that neglects an important part of the subject. Narrative identity offers, in this sense, a remedy to such negligence. His second thesis is that today’s digital media and technologies are closer to the Bourdieusian habitus than to the Ricoeurian narrative identity. In other words, digital machines and technologies are “habitus machines” both in their structure and in their effects.